2023
DOI: 10.1021/acs.jafc.3c01225
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation Products Influence Calpain-1 Functionality In Vitro by Covalent Binding

Abstract: The objective of the current study was to evaluate the effects of lipid peroxidation products, malondialdehyde (MDA), hexenal, and 4-hydroxynonenal (HNE), on calpain-1 function, and liquid chromatography and tandem mass spectrometry (LC-MS/MS) identification of adducts on calpain-1. Calpain-1 activity slightly increased after incubation with 100 μM MDA but not with 500 and 1000 μM MDA. However, calpain-1 activity was lowered by hexenal and HNE at 100, 500, and 1000 μM. No difference in calpain-1 autolysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 90 publications
(171 reference statements)
1
7
0
Order By: Relevance
“…This may suggest that 2-hexenal and 4-hydroxynonenal modify residues near or adjacent to the active site but do not directly modify the residues within the active site. Similar results with calpain-1 were observed, where incubation with malondialdehyde at 100, 500, and 1000 μM had minimal impact on calpain-1 activity and autolysis, while 2-hexenal and 4-hydroxynonenal decreased the activity at all concentration levels tested and slowed down calpain-1 autolysis …”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…This may suggest that 2-hexenal and 4-hydroxynonenal modify residues near or adjacent to the active site but do not directly modify the residues within the active site. Similar results with calpain-1 were observed, where incubation with malondialdehyde at 100, 500, and 1000 μM had minimal impact on calpain-1 activity and autolysis, while 2-hexenal and 4-hydroxynonenal decreased the activity at all concentration levels tested and slowed down calpain-1 autolysis …”
Section: Resultssupporting
confidence: 80%
“…The reactivity and adduction of lipid oxidation products to proteins have been evaluated with mass spectrometry approaches over the last two decades. Specific oxidation product adduction sites on tryptic peptides have been identified in vitro , including 4-hydroxynonenal modifications on lactate dehydrogenase, cytochrome c, , cytochrome c oxidase, hemoglobin, myoglobin, ,,, apomyoglobin, ,, calpain-1, and soy protein isolate, malondialdehyde modifications on pyruvate kinase, calpain-1, and soy protein isolate, and 2-hexenal modifications on model peptides . Many of these studies aimed to explain the mechanisms of the observed changes in protein function due to incubation with lipid oxidation products by identifying and quantifying the location and number of lipid oxidation products.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations